Emerging Concepts in Vector Development for Glial Gene Therapy: Implications for Leukodystrophies - von Jonquieres, Georg; Rae, Caroline D.; Housley, Gary D. (Frontiers in Cellular Neuroscience, 2021)
Central Nervous System (CNS) homeostasis and function rely on intercellular synchronization of metabolic pathways. Developmental and neurochemical imbalances arising from mutations are frequently associated with devastating and often intractable neurological dysfunction. In the absence of pharmacological treatment options, but with knowledge of the genetic cause underlying the pathophysiology, gene therapy holds promise for disease control. Consideration of leukodystrophies provide a case in point; we review cell type - specific expression pattern of the disease - causing genes and reflect on genetic and cellular treatment approaches including ex vivo hematopoietic stem cell gene therapies and in vivo approaches using adeno-associated virus (AAV) vectors. We link recent advances in vectorology to glial targeting directed towards gene therapies for specific leukodystrophies and related developmental or neurometabolic disorders affecting the CNS white matter and frame strategies for therapy development in future.